Efficacy and safety of repeated transcranial magnetic stimulation combined with escitalopram in the treatment of major depressive disorder: a meta-analysis - Liu, Zhang; Yu, Sijia; Hu, Youfan; Wang, Ding; Wang, Shuyu; Tang, Zhaohui; Li, Weihong (Frontiers in Psychiatry, 2024)
Objective: This study was designed to systematically review the efficacy and safety of repeated transcranial magnetic stimulation (rTMS) combined with escitalopram in treating major depressive disorder (MDD). Methods: Databases including PubMed, Embase, Cochrane, Web of Science, CNKI, Wanfang, VIP Journal, and China Biomedical Literature databases were electronically searched for randomized controlled trials of rTMS combined with escitalopram intervention for MDD treatment from the inception of these databases to May 27, 2023. Two reviewers independently screened the studies, extracted the data, and assessed the quality of the included studies. R 4.2.2 was then used for a meta-analysis. Results: In total, 19 articles involving 1,032 patients were included. The results of the meta-analysis showed that Hamilton Depression Rating Scale (HAMD) scores were significantly lower in the group receiving rTMS combined with escitalopram (experimental group) than that in the control group [weighted mean difference (WMD) = -5.30, 95% confidence interval (95% CI): −6.44 to −4.17, P < 0.01]. The response rate of the experimental group was significantly higher than that of the control group [odds ratio (OR): 5.48; 95% CI: 3.72 to 8.07; P < 0.01]. No significant difference in the adverse reaction rate was observed between the two groups (OR: 1.04, 95% CI: 0.71 to 1.52, p = 0.82). Conclusions: Our findings suggest that rTMS combined with escitalopram can benefit patients with MDD in a safe manner, which may help in guiding clinical practice.